2008
DOI: 10.1097/mlg.0b013e31815a9e87
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Stenosis After Placement of Percutaneous Dilational Tracheotomy

Abstract: It has been demonstrated in the literature that with 20 years of experience, the percutaneous dilational tracheotomy procedure is more affordable, faster to perform, and a generally safe procedure when performed under appropriate conditions. Most case series of percutaneous dilational tracheotomy reveal an equal or lower risk of short-term complications than open tracheotomy. This series demonstrates that tracheal stenosis is a potential long-term complication. Longitudinal follow-up of patients undergoing per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The relevance of tracheal ring fractures in the development of tracheal stenosis is obvious but not fully understood. The development of tracheal stenosis after untreated tracheal ring fractures is probable [16, 17], and the possibility of immediate treatment of tracheal ring fragments after tracheal ring fracture may be an advantage of the TED.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of tracheal ring fractures in the development of tracheal stenosis is obvious but not fully understood. The development of tracheal stenosis after untreated tracheal ring fractures is probable [16, 17], and the possibility of immediate treatment of tracheal ring fragments after tracheal ring fracture may be an advantage of the TED.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reported complaints were minor. Moreover, it is difficult to distinguish between complaints (like voice problems or tracheal stenosis) that are really due to the tracheostomy or due to prolonged endotracheal intubation and/or underlying disease [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study reporting five events of stenosis following SDT, the development of stenosis was due to the fracture of the anterior tracheal wall because of compression. 19 SDT and GWDF were similar in terms of midterm (with in situ tracheal tube) and late (after decannulation) outcomes. Late outcomes are always difficult to be evaluated because of the limited percentage of critically ill patients surviving up to removal of tracheostomy and available for followup.…”
Section: Discussionmentioning
confidence: 54%
“…Excluding 1006 non-pertinent titles or abstracts, we retrieved in complete form and assessed according to the selection criteria 34 studies. After excluding 10 articles that were not randomised, [13][14][15][16][17][18][19][20][21][22] twelve articles that had another PDT as comparator [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and seven that were reviews, 1,2,7,35-38 we finally identified five eligible RCTs, [8][9][10]39,40 which were included in the final analysis. …”
Section: Search Resultsmentioning
confidence: 99%